Prognostic implication of sodium nitroprusside vasodilator test in pulmonary hypertension and left heart disease: insights from PUSHON registry. (25th November 2020) - Boretto, P; Bruno, F; Bertaina, M; Bocchino, P; Galluzzo, A; Gatti, P; Peyracchia, M; De Ferrari, G.M
Abstract: Background: Definition of combined post and pre-capillary pulmonary hypertension (Cpc-PH) is controversial, despite involving up to 25% of patients with heart failure with reduced ejection fraction (HFrEF). The 2019 World Symposium on PH focused on conflicting results and potential misleading interpretation of mean transpulmonary gradient (TPG) and diastolic transpulmonary gradient (DPG) in predicting outcomes in type 2 PH patients. A new Cpc-PH definition has been proposed, basing on pulmonary arterial wedge pressure (PAWP) >15 mmHg and pulmonary vascular resistance (PVR) >3 WU. In this setting, the role of vasodilator challenge has marginally been explored. Purpose: This study aims to investigate whether vasodilator test increases prognostic accuracy in PH-LHD comparing to PVR and TPG. Methods: 125 patients with a first diagnosis of PH-LHD were selected within the PUlmonary hypertenSion in rigHt heart catheterization (PUSHON) registry. All patients underwent right heart catheterization and sodium nitroprusside vasodilator infusion. Hemodynamic response was defined as decrease of mean pulmonary arterial pressure (mPAP) <25 mmHg with maintenance of systemic systolic arterial pressure >85 mmHg. Primary endpoint was a composite of cardiac death, heart transplantation and urgent LVAD implant at 2 years. Results: 34 (27%) patients were sodium nitroprusside responders. Normalization of mPAP during acute vasodilator challenge was associated with higher event-free survival at 2 years (HR 2.46, 95% C.I. 1.29–4.69, p=0.006). Responders to nitroprusside showed lower baseline pressure regimens in pulmonary artery (sPAP 56.4±12.9 vs 63.2±12.4 mmHg, p=0.009; mPAP 38.1±6.9 vs 44.7±8.8 mmHg, p=0.001) and lower Wedge Pressure (25.1±6.6 vs 29.8±6.6 mmHg, p=0.001). Also, patients with positive vasodilator test showed better right ventricular function expressed by TAPSE (17.2±4.3 vs 15.4±3.8 mm, p=0.05) and higher EF (34.6±15.3% vs 28.1±13.1%, p=0.023). Interestingly, nitroprusside responders exhibited lower DPG (−0.11±5.30 vs 2.04±5.21 p=0.04). At multivariate analysis PVR and TPG ≥12 mmHg fail to independently predict primary endpoint, while positive vasodilator response was independently associated with better outcome (OR 0.22, 95% C.I. 0.09–0.52, p=0.001). The same results were confirmed in the Cpc-PH subgroup (OR 0.54, 95% C.I. 0.08–0.78, p=0.018). Conclusions: Nitroprusside vasodilator response was associated with a higher event-free survival at 2 years follow-up in our cohort of patients with PH-LHD. Larger studies with prospective hemodynamic evaluations are needed to support our hypothesis. Funding Acknowledgement: Type of funding source: None